2020
DOI: 10.1590/0004-282x20200089
|View full text |Cite
|
Sign up to set email alerts
|

Neurological consultations and diagnoses in a large, dedicated COVID-19 university hospital

Abstract: Background: More than one-third of COVID-19 patients present neurological symptoms ranging from anosmia to stroke and encephalopathy. Furthermore, pre-existing neurological conditions may require special treatment and may be associated with worse outcomes. Notwithstanding, the role of neurologists in COVID-19 is probably underrecognized. Objective: The aim of this study was to report the reasons for requesting neurological consultations by internists and intensivists in a COVID-19-dedicated hospital. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 26 publications
(32 reference statements)
3
44
0
2
Order By: Relevance
“…The SARS-CoV-2 virus is a respiratory pathogen and hence complications affecting the brain could be secondary to hypoxia and metabolic derangements. However, the current paper by Studart-Neto et al 1 finds, and other similar descriptions emerging from around the world show that the vast majority of patients have other types of neurological involvement, some of which can be severe 2,3,4,5 . While loss of smell and taste is the most common symptom observed, nearly half of the patients hospitalized have some form of encephalopathy and about a fifth of the patients develop strokes 6,7 .…”
supporting
confidence: 57%
“…The SARS-CoV-2 virus is a respiratory pathogen and hence complications affecting the brain could be secondary to hypoxia and metabolic derangements. However, the current paper by Studart-Neto et al 1 finds, and other similar descriptions emerging from around the world show that the vast majority of patients have other types of neurological involvement, some of which can be severe 2,3,4,5 . While loss of smell and taste is the most common symptom observed, nearly half of the patients hospitalized have some form of encephalopathy and about a fifth of the patients develop strokes 6,7 .…”
supporting
confidence: 57%
“…Fifty-five patients were included in the final analysis (Flowchart 1). All patients were also included in a previous study that evaluated reasons for neurology consultation in Hospital das Clínicas [7]. Detailed clinical and ancillary data of patients with encephalopathy were not provided in that report.…”
Section: Resultsmentioning
confidence: 99%
“…Agitation and confusion occur commonly in patients with acute respiratory distress syndrome in COVID-19 [6]. In a previous series of consecutive COVID-19 patients evaluated by neurologists in a dedicated COVID-19 tertiary referral hospital, encephalopathy was the leading reason for a neurology consultation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although COVID-19 is typically characterized by respiratory symptoms, numerous clinical studies have shown that patients infected with SARS-COV-2 are associated with acute injuries to external pulmonary organs, including the heart, digestive tract, liver, kidney and nervous system [6][7] .More and more clinical evidence indicates that SARS-COV-2 may invade the central nervous system. A retrospective analysis of 214 patients with COVID-19 found that 78 (36.4%) had nervous system involvement, and 28.2% of them had severe central nervous system injury [8] .Studart-neto A et al retrospectively analyzed 1208 patients with COVID-19 and found that 89 (7.4%) presented neurological manifestations, including encephalopathy (44.4%), stroke (16.7%), epilepsy (9.0%), neuromuscular disease (5.6%), other acute brain injury (3.4%), and other mild non-speci c diseases (11.2%) [9] .Takeshi et al detected SARS-COV-2 RNA in cerebrospinal uid specimens, providing direct evidence for the nerve invasiveness of SARS-COV-2 [10] .There are three main types of COVID-19 nervous system involvement :(1) central nervous system involvement, such as dizziness, headache, disturbance of consciousness, acute cerebrovascular disease, and epilepsy;(2) peripheral nervous system involvement, including anosmia, decreased taste, decreased vision, and neuralgia;(3) skeletal muscle injury [11][12] .COVID -19 possible mechanisms include: nerve injury by angiotensin converting enzyme (ACE2) receptor function, blood and break through the blood brain barrier, through the way such as olfactory nerve attack the nervous system [13][14] .…”
Section: Introductionmentioning
confidence: 99%